Faculty Views of Student Evaluation of College Teaching - Nasser, Fadia; Fresko, Barbara (Assessment & Evaluation in Higher Education, 2002)
The literature abounds with psychometric studies of course evaluation measures and articles debating the merits of student ratings of instruction, but little research has focused on faculty perceptions of this procedure. In the present study faculty perceptions are explored at a teachers' college where evaluation is carried out annually on a sample of courses. The sample includes 101 instructors who completed the research questionnaire. Faculty attitudes reflected a broad range of responses towards validity of student ratings, and their usefulness for improving instruction. Although overall attitudes were mildly positive, few instructors reported changing instruction as a result of student ratings. Moreover, few supported sending evaluation results directly to college administrators or publishing them for student consumption.